Numerical modeling of the contact effect on the parameters of cracking in a 2D Fatigue Fretting Model (Fracture and Structural Integrity, 2021)
The objective of this work is to study the effects of contact parameters on the cracking parameters of a specimen and a pad assembly. These parameters have been studied and evaluated by the finite element method analysis in two dimensions fretting fatigue model through the Abaqus calculation code. Different values ​​of the coefficient of friction of 0.1, 0.3 and 0.6 were applied on the various lengths in contact for a = 0.1, 0.5 and 1mm. Thus, on the various values ​​of angle of orientation of the crack equal to 15 °, 30 ° and 45 °. In addition, elements of the type (CPE4R) and the criterion of maximum tangential stress were applied. The curves of the crack parameters such as the SIF coefficients and the integral J were obtained and discussed.
Keywords: 2D crack; FEM; Fretting fatigue; Stress intensity factor (SIF); Coefficient of friction (COF)